2009
DOI: 10.1007/s00262-009-0802-8
|View full text |Cite
|
Sign up to set email alerts
|

IL-17E, a proinflammatory cytokine, has antitumor efficacy against several tumor types in vivo

Abstract: Interleukin-17E (IL-17E) belongs to a novel family of cytokines that possess significant homology to IL-17. IL-17E has potent inflammatory effects in vitro and in vivo. Overexpression of IL-17E in mice results in a T helper-2 (Th2)-type immune response, which includes the expansion of eosinophils through the production of IL-5, and elevated gene expression of IL-4 and IL-13 in multiple tissues. In this study, we show that IL-17E has antitumor activity in vivo, a previously unrecognized function of IL-17E. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 47 publications
2
78
1
Order By: Relevance
“…Understanding the molecular mechanisms involved in the cross-talk between eosinophils and CRC cells would certainly contribute to improve the existing knowledge of the immunogenic characteristics of the disease and may have a major impact in the development of novel therapeutic targets. 6,9,11,26,28,29,[31][32][33][34][35] In the case of CRC, eosinophil recruitment, activation and survival was suggested to be dependent on local production of IL-5 by tissue resident eosinophils 36 and active damage associated molecular pattern (DAMP) molecules, namely high mobility group box 1 (HMGB1), in the context of tumour cell necrosis. 32 Surprising findings have been achieved on the role of eotaxins in eosinophil chemoatraction to CRCs, since low numbers of tissue eosinophils are found both in primary CRCs 10,37 and liver metastases, 37 albeit not always associated with low levels of tissue eotaxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the molecular mechanisms involved in the cross-talk between eosinophils and CRC cells would certainly contribute to improve the existing knowledge of the immunogenic characteristics of the disease and may have a major impact in the development of novel therapeutic targets. 6,9,11,26,28,29,[31][32][33][34][35] In the case of CRC, eosinophil recruitment, activation and survival was suggested to be dependent on local production of IL-5 by tissue resident eosinophils 36 and active damage associated molecular pattern (DAMP) molecules, namely high mobility group box 1 (HMGB1), in the context of tumour cell necrosis. 32 Surprising findings have been achieved on the role of eotaxins in eosinophil chemoatraction to CRCs, since low numbers of tissue eosinophils are found both in primary CRCs 10,37 and liver metastases, 37 albeit not always associated with low levels of tissue eotaxins.…”
Section: Discussionmentioning
confidence: 99%
“…35 Thus, eosinophils may be engaged in the anti-tumour effect of IL-17E, and IL-17E was endorsed as a putative effective therapy in colon adenocarcinoma. 35 In addition to the aforementioned molecular mechanisms, the relation between eosinophils and other immune cells raises the hypotheses that eosinophils may also exert their action via other cells and vice-versa. 9,15,19 The interaction between eosinophils and other immune cells has been recognized.…”
mentioning
confidence: 99%
“…Interestingly, B cells comprised 57% of infiltrating cells in benign glands; this number was significantly reduced in malignant glands. Inflammatory cytokines including TNFα, IL-6, and IL-8 play an important role in oncogenesis and tumor progression, whereas other kinds of cytokines including IL-17E have antitumour activity [26,27,28,29]. Thus, B cells contribute to both tumor progression and suppression.…”
Section: Discussionmentioning
confidence: 99%
“…33 More recently, it has been demonstrated that IL-25 (synonym IL-17E), which is also released by eosinophils, exhibits antitumoral activity and leads to eosinphilia in a colorectal cancer xenograft model. 34 IL-25 may induce the expansion of eosinophils through IL-5 as well as elevated levels of IL-4 and IL-13, but also directly induce apoptosis of cancer cells. 35 Our study has strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%